Language planning and policy - Xonzoda , Maxramqulova; Ergasheva , Guli (The Lingua Spectrum, 2025)
In this article, the concept of language policy and its planning, its development, how language policy and its planning practices were carried out on the example of different continents and countries in those regions will be explained. During the language policy and its planning, the process of various skills and the obstacles they face are highlighted. Also, what shortcomings were noticed during these activities, how they were eliminated, and what achievements were made. The study of language planning and policy (LPP) examines how social, educational, and political institutions purposefully shape language use, status, and structure. It entails initiatives to advance, control, or modify language in order to achieve social, political, or cultural objectives. Language status planning, which determines which languages are given official status; corpus planning, which creates or standardises language structure; and acquisition planning, which influences language instruction and learning, are among the important topics covered by LPP.